Longevity in a population of aged mice - Richard Costanzo; Maggie Sager; Thien Thanh Nguyen (Open Science Framework, 2022)
This project contains data and analysis of longevity from a colony of P2 (P2-IRES-tau lacZ) transgenic mice maintained over a time period of 16 years. P2 mice allow for the labeling of a specific (P2) odorant receptor type and have been used extensively in studies of the olfactory system. A manuscript summarizing the longevity data was submitted to the journal "Chemical Senses" in 2014. The journal editors considered the work as "outside the scope of the journal" and returned the manuscript without review. Given that the data may be of some use to the research community a decision was made to post the data and the manuscript on the OSF website.
Keywords: age; aged mice; breeding; longevity; mice; p2 mice